V. A. GRAICUNAS AND THE SPAN OF CONTROL - Urwick, L. F. (Academy of Management Journal, 1974)
The article discusses the author's opinion on the span of control principle of organization conceptualized by Vytautas Andrius Graicunas. In business, the principle does not apply at the lowest level of supervision. Workers are engaged in groups on a repetitive operation and control of the work is exercised by individual output figures. In many industrial operations, an unofficial leadership is exercised by senior workers who are not given any official status or rank. There are many instances in business in which the principle is ignored with disastrous consequences to the business or the individual.